Εκφοβισμός/θυματοποίηση και μοναξιά του παιδιού στην ομάδα των συνομηλίκων και στη δυαδική φιλία - Γαλανάκη, Ε.; Ε Αμανάκη; Ε Νοικοκύρη (Παιδαγωγική Επιθεώρηση, 2009)
Bullying, as a prevalent phenomenon in Greek schools, is a stressful situation, often with a traumatic character. The aim of this research was to examine the associations between bullying/victimization and loneliness in the peer group (social loneliness) and the dyadic friendship (emotional loneliness). Participants were 208 fifth-grade students from schools located in the center of Athens. They completed the Olweus Bully/Victim Questionnaire-Revised Edition (Olweus, 2006) and the Peer Network and Peer Dyadic Loneliness Scale (Hoza, Bukowski, & Beery, 2000), which showed adequate internal consistency. Linear regression analyses indicated that the tendency to be bullied was associated with loneliness in the peer group and in the dyadic friendship, whereas the tendency to bully was not associated with any dimension of loneliness. Bullies/victims were the children experiencing the highest loneliness of all the other groups. Sexual victimization, social exclusion, and stealing/damaging belongings were significantly related to the various dimensions of loneliness. More boys than girls were bullies/victims, but no gender difference was found for loneliness. Discussion focuses on the importance of knowing the personal, subjective experience of bullies and victims, as well as on the implications of these findings for school-based interventions.